(untitled) (Malaysian Journal of Learning and Instruction, 2025)
Purpose - This study explores how the integration of digital technology in Islamic education impacts primary school students’ learning, from the perspective of Islamic education teachers. It aims is to highlight the potential benefits of digital integration in the classroom and to address the gaps between Islamic education teachers’ perceptions and students’ digital competencies. Methodology - Using a qualitative case study design, the study involved five Islamic education teachers proficient in digital technology, selected through a snowball sampling technique. Data were collected via interviews, classroom observations, and audio-visual analysis. Thematic analysis was conducted using NVIVO 14 software, guided by the framework of Miles, Huberman, and Saldaña (2020). Trustworthiness was ensured through triangulation, member checking, peer review, detailed audit trails, and inter-rater reliability. Findings - The analysis revealed five major themes: enhancing motivation, fostering independent learning, revealing digital prowess, optimizing digital interaction, and promoting collaboration. These themes reflect students’ increased engagement and competitiveness, development of self-directed learning skills, mastery of digital tools, improved communication—including English language—and collaborative teamwork in learning tasks. Significance - This study offers Islamic education teachers a renewed perspective on the value of integrating digital technology into their teaching practices. By showcasing practical insights and pedagogical strategies, the findings aim to empower educators to create dynamic, student-centred learning environments aligned with the demands of 21st-century education and national aspirations for a digitally literate generation.